Peroxisome proliferator-activated receptor (PPAR)γ is highly expressed in normal human pituitary gland - Bogazzi, F.; Russo, D.; Locci, M. T.; Chifenti, B.; Ultimieri, F.; Raggi, F.; Viacava, P.; Cecchetti, D.; Cosci, C.; Sardella, C.; Acerbi, G.; Gasperi, M.; et al. (Journal of endocrinological investigation, 2005)
Expression of peroxisome proliferator-activated receptor (PPAR)gamma in normal pituitary seems to be restricted to ACTH-secreting cells. The aim of the study was to evaluate the expression of PPARgamma in normal human pituitary tissue and to study its localization in the pituitary secreting cells. Normal pituitary tissue samples were obtained form 11 patients with non-secreting adenoma who underwent surgical excision of the tumor. Expression of PPARgamma was evaluated by immunostaining and western blotting; localization of PPARgamma in each pituitary secreting cell lineage was evaluated by double immunofluorescence using confocal microscopy. Pituitary non-functioning adenomas served as Controls. PPARgamma was highly expressed in all pituitary samples with a (mean +/- SD) 81 +/- 6.5% of stained cells; expression of PPARgamma was confirmed by western blotting. Non-functioning pituitary adenomas had 74 +/- 11% PPARgamma positive cells. Expression of PPARy was either in cytoplasm or nuclei. In addition, treatment of GH3 cells, with a PPARgamma ligand was associated with traslocation of the receptor from cytoplasm into the nucleus. Double immunostaining revealed that every pituitary secreting cell (GH, TSH, LH, FSH, PRL and ACTH) had PPARgamma expressed. The present study demonstrated that PPARgamma is highly expressed in every normal pituitary secreting cell lineage. It can translocate into the nucleus by ligand binding; however, its role in pituitary hormone regulation remains to be elucidated.